Pengaruh Real Mismatch terhadap Upah Pekerja di Indonesia - Pyansahcilia, Jawani Eka; Handayani, Dwini (Jurnal Ekonomi Kependudukan dan Keluarga, 2026)
This study aims to analyze the effect of real mismatch on the wages of workers with medium and higher education levels in Indonesia using the ordinary least squares (OLS) method. The data used in this study are derived from the National Labor Force Survey (Sakernas) conducted in August 2023 to identify instances of mismatch and analyze its impact on workers' wages. In 2023, the incidence of vertical mismatch only was recorded at 14.58 percent, horizontal mismatch only at 31.73 percent, and real mismatch reached 25.24 percent. The estimation results indicate that workers experiencing vertical mismatch only receive a wage premium, applicable to both undereducated only and overeducated only workers. In contrast, workers experiencing horizontal mismatch only and real mismatch incur a wage penalty. Moreover, differences in the patterns of mismatch status effects on wages were observed when the estimation was conducted on subsamples based on ISCO-08 skill levels, while also considering individual and occupational characteristics. These findings provide valuable insights into the impact of educational level and field mismatch on workers' welfare through wages, with relevant policy implications for improving efficiency and alignment between education and labor market needs.